The whole package ebook - Harte, Marie (Veteran Movers, 2019)
We thought we were done being heroes... When I first started my moving company—Vets on the Go!—after getting out of the Marines, I wanted to help my brother Cash and other veterans adjust to civilian life. But then someone filmed Cash taking down a robber, and no sooner could you say "viral video," than Vets on the Go became the go-to moving company. Everyone wants to hear our story. But now, I can't keep up with the deluge of interest. Enter PR expert Naomi Starr. She's trying to revive her career, and I need her help. Unfortunately, she's got a "never mix business with pleasure" philosophy that is putting a serious crimp in the chemistry between us. I need to unseal her secrets and expose her to all the hot and dirty things she's been missing out on with me. Maybe then she'll let go of her misgivings and trust that I'm the whole package...